In situ polymerization of biodegradable poly(butylene-co-succinate terephthlate) nanocomposites and their real-time tracking of microstructure. (29th September 2015) - Wei, Zhenzhen; Lin, Jinyou; Wang, Xueli; Huang, Liqian; Yu, Jianyong; Li, Faxue
Abstract: The further development and application of biodegradable poly(butylene-co-succinate terephthlate) (PBST) copolymer was restricted due to the slow crystallization during fabrication and the unstable morphologies during utilization. Prospectively, employing silica nanoparticles (NPs) as versatile nanofillers will notably promote the advances of PBST and broaden its scope of application. Here, we present a facile method for the generation of PBST/silica nanocomposites via in situ polymerization. Incorporating silica NPs into polymer matrices endows the resultant composites with improved thermal, mechanical properties and accelerated crystallization during cooling from the melts, which has been confirmed by the in situ X-ray measurements. The structural development of PBST and its nanocomposites during cooling is proposed. Meanwhile, the crystal and lamellae structural evolution of PBST nanocomposites during uniaxial stretching is also investigated. The transition of crystal forms occurs during stretching but is delayed compared with that of pristine copolymer, and the formation of lamellar structure is highly dependent on the temperature. Studies of structural responses of PBST nanocomposites to dynamic conditions are beneficial to tailor the properties of PBST products, and also open the door to PBST nanocomposites with other nanofillers for various applications.